Methode des elements finis specifique aux ossatures mixtes acier-beton avec glissements et grands deplacements - Zhao, Bin; Aribert, Jean-Marie (European Journal of Computational Mechanics, 1996)
In order to analyse the behaviour of braced or unbraced steel and concrete composite frames with full or partial shear connections, an original finite element model using approximate updated Lagrangian formulation is developed. The choice of slip as a nodal degree of freedom leads to the approximate kinonatic transformations which are necessary for the assemblage of matrices of steel and concrete parts (stiffness matrices and vectors of nodal forces). After the demonstration of the validity of the model for different aspects (geometrical nonlinearity, material non linearity, slip, etc), some applications of the model show clearly the improvement in lateral stiffness and ultimate resistance of composite fra-mes compared to the same frame but composed of only steel members.